The spatial and temporal distribution of dendrite fragmentation in solidifying Al-Cu alloys under different conditions. (December 2016) - Liotti, E.; Lui, A.; Kumar, S.; Guo, Z.; Bi, C.; Connolley, T.; Grant, P.S.
Abstract: The directional columnar solidification of Al-Cu alloy dendrites was studied in-situ by synchrotron X-ray radiography to investigate the spatial and temporal distribution of dendrite fragmentation, without and with an applied pulsed electromagnetic field (PEMF) and in different solidification directions. The differing arrangements had a strong and reproducible influence on fragmentation behaviour that was rationalised using a model of solute-driven re-melting of dendrite arms in microstructural regions of high vulnerability. Although absolute rates of fragmentation varied, all the fragmentation distributions had a characteristic peak in fragmentation rate at a distance of 500–800 μm into the mushy zone. Consistent with the need for solute-rich liquid flow for dendrite root re-melting, this peak was explained to occur under conditions where there was both comparatively steep liquid solute concentration gradients, measured directly from the radiographs, and relatively high permeability of the dendrite network to liquid flow. Graphical abstract: